2015
DOI: 10.1016/j.nbd.2015.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Reactive oxygen species mediate cognitive deficits in experimental temporal lobe epilepsy

Abstract: Cognitive dysfunction is an important comorbidity of temporal lobe epilepsy (TLE). However, no targeted therapies are available and the mechanisms underlying cognitive impairment, specifically deficits in learning and memory associated with TLE remain unknown. Oxidative stress is known to occur in the pathogenesis of TLE but its functional role remains to be determined. Here, we demonstrate that oxidative stress and resultant processes contribute to cognitive decline associated with epileptogenesis. Using a sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
102
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 90 publications
(113 citation statements)
references
References 53 publications
(77 reference statements)
6
102
0
Order By: Relevance
“…The increases in pro-inflammatory cytokines follows a similar pattern as the production of ROS, mitochondrial complex I inactivation, post-translational modifications and occurrence of mitochondrial respiration deficits in chemoconvulsant models of TLE (Jarrett et al, 2008; Pearson et al, 2015; Rowley et al, 2015; Ryan et al, 2012). It is also somewhat reminiscent of the time course of alterations in tissue redox status following kainic acid or pilocarpine-induced SE (Ryan et al, 2014; Waldbaum et al, 2010) suggesting a relationship between ROS production, redox state and inflammation.…”
Section: Discussionmentioning
confidence: 79%
See 3 more Smart Citations
“…The increases in pro-inflammatory cytokines follows a similar pattern as the production of ROS, mitochondrial complex I inactivation, post-translational modifications and occurrence of mitochondrial respiration deficits in chemoconvulsant models of TLE (Jarrett et al, 2008; Pearson et al, 2015; Rowley et al, 2015; Ryan et al, 2012). It is also somewhat reminiscent of the time course of alterations in tissue redox status following kainic acid or pilocarpine-induced SE (Ryan et al, 2014; Waldbaum et al, 2010) suggesting a relationship between ROS production, redox state and inflammation.…”
Section: Discussionmentioning
confidence: 79%
“…, hydrogen peroxide, peroxynitrite and lipid peroxides. We have previously shown that 5mg/kg, s.c. injection of MnIIITDE-2-ImP5+ 60 min after pilocarpine SE did not interfere with SE (Pearson et al, 2015). Using this dosing paradigm, we first confirmed the ability of this compound to inhibit SE-induced oxidative stress by measuring the levels of the most abundant non-protein thiol glutathione (GSH) and its oxidized form GSSG.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, a French pharmacovigilance database study concluded that even newer antiepileptic drugs (AED) like topiramate, pregabalin, and levetiracetam have a negative impact on memory [6]. Oxidative stress is considered to play an important role in epileptogenesis and cognitive deficits [7].…”
Section: Introductionmentioning
confidence: 99%